Yield and quality of inflorescences of 'Golden Torch' heliconia in different shaded environments - Rafaela R. de Souza; Márkilla Z. Beckmann-Cavalcante; Alcilane A. Silva; Everaldo M. da Silva; Leonardo P. da S. Brito; Adriano O. Silva (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT Light is one of the factors that most affect crop growth and yield. However, the control of light intensity is difficult, because, under certain environmental conditions, light energy may exceed or limit the capacity of plants to use it. In this sense, the productive behavior of plant species in shaded environments needs to be known. This study aimed to evaluate the effect of different shaded environments with black shade nets [0 (full sun), 35 and 50%, and overlap 35 + 50% shading nets] on flowering, yield and quality of inflorescences of Heliconia psittacorum (cv. 'Golden Torch'). The shaded environments caused a reduction in the number of days for inflorescence emergence and in the cycle of H. psittacorum (cv. 'Golden Torch'). The yield and quality of inflorescences of plants grown under full-sun conditions (0% shading) were impaired. The results indicate that, for a better management of the crop environment, aiming yield and quality of inflorescences of H. psittacorum (cv. 'Golden Torch'), the use of black shade nets with 50% shading is recommended.